Analysis Intention of Farmer Card Utiliization Using Theory of Planned Behavior - Mutiara Mar Atu Sholihah; Moh Djemdjem Djamaludin (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2018)
One of the Indonesia government’s policies in an effort to increase production and productivity of agricultural commodities is providing subsidized fertilizer for farmers. Currently, the government implements the farmer card program as an effort to facilitate farmers in purchasing subsidized fertilizers. This program will be implemented simultaneously in 2020, but in 2018 there are some areas that already implemented the farmer card system as a trial area. This study aims to analyze the farmer intention in term of using a farmers card in Rancaekek. The analysis used is Theory of Planned Behavior (TPB), statistical analysis, and structural equation modeling (SEM). The research design used cross-sectional study. The sampling method used probability sampling - simple random sampling. 100 farmers were interviewed in sub-district Rancaekek from 1492 farmers. Based on the statistical analysis using SEM showed that attitude toward behavior, subjective norm, and perceived behavioral control are significant and have positive effects on the intention of using farmers card. So that, the higher farmers attitude toward behavior, subjective norm, and perceived behavioral control, the higher the farmer intention of using farmer card. All of the variable Theory of Planned Behavior is a determinant factor in influencing the intention of using the farmer card. Attitude toward behavior has the largest influence on farmers intention of using farmer card and subjective norm has the smallest influence in farmers intention of using farmer card.